Pengaruh Leverage, Profitabilitas, Dan Likuiditas Terhadap Tax Avoidance (Studi Empiris Pada Perusahaan Sektor Teknologi yang Terdaftar di BEI 2022-2024) - Al Hadiid; Rahmat Kurniawan (CV. ITTC INDONESIA, 2026)
Tax avoidance has become an increasingly important issue in corporate tax management, as it is carried out legally byexploiting loopholes in tax regulations. This is frequently observed in companies within the technology sector, which arecharacterised by high growth, significant funding requirements and a predominance of intangible assets, all of which havethe potential to influence a company’s tax burden management strategy. This study aims to analyse the influence of leverage,profitability and liquidity on tax avoidance among technology sector companies listed on the Indonesia Stock Exchange(IDX) for the period 2022–2024. This study employs a quantitative approach using an associative research design. The studypopulation comprises all technology sector companies listed on the IDX during the observation period (2022–2024). Thesample was determined using purposive sampling based on specific criteria, resulting in 110 observations that met the study’seligibility criteria. The data used were secondary data obtained from the companies’ annual financial statements andanalysed using multiple linear regression with the aid of SPSS version 25 software. The research findings indicate thatleverage and profitability have a positive and significant effect on tax avoidance, whilst liquidity has no significant effect ontax avoidance. Taken together, leverage, profitability and liquidity have a significant effect on tax avoidance. These findingssuggest that a company’s capital structure and its ability to generate profits are the key factors influencing tax avoidancepractices in the technology sector. It is hoped that the findings of this study will provide useful insights for companymanagement, investors and regulators in formulating policies that enhance tax compliance and enable more effectivemanagement of corporate financial structures